Parasitic Study of Indian Major Carp, Labeo rohita (Hamilton, 1822) in Selected Districts of West Bengal, India - Ramudu, Kurva Raghu; Chinna Rajesh, Sandya; Dash, Gadadhar (International Journal of Bio-resource and Stress Management, 2023)
The work was conducted to isolate and identify different parasites from Labeo rohita, severity of infestation and to find out Parasitic Frequency Index (PFI, %) monthly, seasons and length wise from different selected districts of West Bengal, India. An investigation was made on Rohu (Labeo rohita), such way that the selected districts were had more potential fishery resources, easy to collect samples from those districts and easy transportation of collected samples to laboratory. Approximately 325 fishes were observed in between April 2012 to March 2013. The infested fishes suffered mainly from respiratory problems, blackness of the skin and mortalities. The present study revealed that the parasitic infestations were found to be the major problem in cultivable fish ponds of West Bengal. In the present study, the isolated parasites were Myxobolus sp., Thelohanellus sp., Trichodina sp., Dactylogyrus sp., Gyrodactylus sp., Nematodes, Argulus sp., Lernea sp., Chilodonella sp., Costia sp., Ichthyoptherius multifilus, development stagesand unidentified Crustaceans. Severity of (infestation) all parasites were found to be more. We were found that Myxobolus sp., Thelohanellus sp., prevalence were highest in winter (72% and 56% respectively). Dactylogyrus sp. and Gyrodactylus sp. were more in rainy season and spring respectively (72% and 38% respectively). Chilodonella sp., Costia sp. and Ichthyoptherius multifilus were found high prevalence in spring season. 1 cm to 30 cm length group fishes were more infested with the parasites compare to 30.5 cm to 50 cm length groups.